A mulberry 9-cis-epoxycarotenoid dioxygenase gene MaNCED1 is involved in plant growth regulation and confers salt and drought tolerance in transgenic tobacco - Zhu, Panpan; Li, Ruolan; Fan, Wei; Xia, Zhongqiang; Li, Jun; Wang, Chuanhong; Zhao, Aichun (Frontiers in Plant Science, 2023)
The phytohormone abscisic acid (ABA) is vital in regulating root elongation, seed germination, and abiotic stress responses in plants. Conversely, the mechanisms of ABA in mulberry root growth, seed germination, and abiotic stress responses are poorly understood. Here, we reported that exogenous ABA and drought treatment inhibited the growth of mulberry seedlings but significantly increased the ratio of root/stem. Inhibition of ABA synthesis by fluridone and sodium tungstate resulted in the decrease of root/stem ratio. We also showed that the expression of MaNCED1 in the root was strongly induced by drought and salt stress. Increasing the expression of MaNCED1 in tobacco using overexpression leads to increased root elongation and reduced seed germination. Compared with the wild type, the accumulation of H2O2 and MDA was reduced, while the POD activity and proline content was increased in the transgenic plants after drought and salt treatment. Further studies revealed increased resistance to drought and salt stress in MaNCED1 overexpressed tobaccos. Meanwhile, the auxin and ethylene signal pathway-related gene expression levels increased in MaNCED1 overexpressed tobaccos. This study demonstrated the roles of mulberry MaNCED1 in regulating plant development and abiotic stress responses. It gave further insights into the coordinated regulation of ABA, auxin, and ethylene in seed growth and germination.